(untitled) (Research, Society and Development, 2025)
Nasal bone agenesis is a rare condition with uncertain causes, characterized by the congenital absence of the nasal bone and may be associated with several syndromes and significant facial malformations. Given the rarity of the condition, this study aims to describe a case of nasal arrhinia identified at the Alzira Velano University Hospital, contributing to research and understanding of the diagnosis, treatment, and follow-up of arrhinia. The condition was diagnosed intrauterinely through fetal ultrasound. At birth, the physical examination revealed the absence of the nasal bone, as well as alterations in the adjacent structures. Imaging tests, such as radiography and computed tomography of the face, were requested to better understand the bone and tissue involvement. The proposed treatment involved a multidisciplinary team, with referral to the otorhinolaryngology and speech-language pathology services. A subsequent discussion and literature review on nasal bone agenesis were conducted, focusing on diagnostic challenges and possible current therapies. This work highlights the importance of early diagnosis for adequate management of the condition in a multidisciplinary manner, with the aim of providing a better quality of life to the patient, in addition to emphasizing the need for further studies to better understand this rare craniofacial malformation.